1980
DOI: 10.1530/acta.0.0930356
|View full text |Cite
|
Sign up to set email alerts
|

Studies on changes in the concentration of serum adrenal androgens in pubertal twins

Abstract: A cross-sectional study was undertaken to investigate the correlation of the level of serum adrenal androgens with clinical signs of puberty and to assess the participation of genetic factors in the onset and progression of puberty. Serum concentrations of 11-deoxy-17\x=req-\ ketosteroids (11 -deoxy-17-KS), dehydroepiandrosterone (DHEA) and androstenedione (4-A-dione) were measured in 74 monozygotic and 24 dizygotic twin pairs during the years of puberty. The mean serum concentrations of the adrenal androgens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 10 publications
2
14
0
1
Order By: Relevance
“…There was no increase in the prevalence of balding in this U.S. population of male first-degree relatives. DHEAS levels were highly correlated between brothers and their proband sisters, consistent with a heritable trait (26)(27)(28)36). The same putative defect in steroidogenesis that we reported in the sisters of women with PCOS (12) could account for the observed DHEAS elevations in the brothers of PCOS probands.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was no increase in the prevalence of balding in this U.S. population of male first-degree relatives. DHEAS levels were highly correlated between brothers and their proband sisters, consistent with a heritable trait (26)(27)(28)36). The same putative defect in steroidogenesis that we reported in the sisters of women with PCOS (12) could account for the observed DHEAS elevations in the brothers of PCOS probands.…”
Section: Discussionsupporting
confidence: 85%
“…There is a decline in circulating DHEAS levels with age (13,14,25), but this phenomenon was controlled for statistically in our analysis. Previous studies have suggested that there is a significant heritable component to circulating DHEAS levels in normal individuals (26)(27)(28). The heritability for DHEAS, however, has been found to be much less for men than for women (27), and heritability has also been noted to be stronger for T levels (26,27,29).…”
Section: Discussionmentioning
confidence: 98%
“…Various data support the fact that inheritance plays a significant role in determining the circulating AA levels in normal individuals [93][94][95][96]. Circulating AA levels and their response to ACTH are highly individualized, compared to their secretion of glucocorticoids in normal women [97].…”
Section: Heritability Of Adrenal Steroidogenesis In Pcosmentioning
confidence: 95%
“…Enfin la survenue de cas familiaux de pubarche pr6coce [63], la plus grande similarit~ du timing et du d6veloppement de l'adr6narche observ6e chez les jumeaux monozygotes que chez les jumeaux dizygotes [2], et le fait que chez les enfants pr6-sentant un retard pubertaire simple, le retard d'adr6narche n'est qu'une des composantes d'un retard de croissance et de d~veloppement, sugg6rent fortement que la maturation du cortex surr~nal est, en partie tout au moins, sous le contr61e de facteurs g~n~tiques.…”
Section: Relations Entre Adrenarche Et Gonadarcheunclassified